Pd-Based Membranes for Hydrogen Separation: Review of Alloying Elements and Their Influence on Membrane Properties. Issue 2 (3rd April 2017) - Conde, Julio J.; Maroño, Marta; Sánchez-Hervás, José María
Abstract : Dense palladium membranes have increasing interest for ultra-pure hydrogen production compared to established technologies such as pressure swing adsorption and cryogenic distillation, allowing the separation in one step with no associated energy consumption. Alloying elements are used in combination with palladium in these membranes to change the membrane properties. This article presents a review of palladium alloy membranes for hydrogen purification, including permeability data and other relevant characteristics of the alloys. Further developments in this research field are expected to focus on the use of ternary alloys with enhanced physical and chemical properties, and the use of computational methods to enable a faster screening of promising alloys.